Diretrizes para seleção de projetistas e avaliação da prestação do serviço de projeto de edificações na visão do contratante - Paula, Nathália de (Universidade Federal de São Carlos, 2009)
The design-product has great importance in Construction, Engineering and Architecture area, as much for its enterprise success strategic function, as for becoming possible the building materialization. Evaluating the quality of the design service rendering (DSR) can denote improvements in the design-product quality and, therefore, in the final product (building). Questions or systemized quality criteria related to DSR quality, with comments, degrees or grades/weights attribution, elaborated from the contractors of these services can allow the DSR evaluation, making possible the designer selection and the performance evaluation of contracted designers. The aim of this work is to propose a set of direction guidelines to designers selection and DSR evaluation in the contractor view. The literature review and case studies were carried out in four construction and incorporation companies and three design companies from São Paulo city. The results show that the constructors and incorporators have practices for selection and evaluation of designers. Two design companies have practices to evaluation of the contractor client satisfaction. In essence, the types of evaluation mentioned designers evaluation and evaluation of the contractor client satisfaction have the same aim: evaluating the DSR. The observation of these practices and the literature review contributed for the elaboration of guidelines to the designers selection and the evaluation of the design service rendering.
Keywords: Projetos de engenharia; Projetos de edificações; Gestão de projetos; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL